Glucose transportation in the brain and its impairment in Huntington disease: one more shade of the energetic metabolism failure? - Morea, Veronica; Bidollari, Eris; Colotti, Gianni; Fiorillo, Annarita; Rosati, Jessica; De Filippis, Lidia; Squitieri, Ferdinando; Ilari, Andrea (Amino acids, 2017)
Huntington’s disease (HD) or Huntington’s chorea is the most common inherited, dominantly transmitted, neurodegenerative disorder. It is caused by increased CAG repeats number in the gene coding for huntingtin (Htt) and characterized by motor, behaviour and psychiatric symptoms, ultimately leading to death. HD patients also exhibit alterations in glucose and energetic metabolism, which result in pronounced weight loss despite sustained calorie intake. Glucose metabolism decreases in the striatum of all the subjects with mutated Htt, but affects symptom presentation only when it drops below a specific threshold. Recent evidence points at defects in glucose uptake by the brain, and especially by neurons, as a relevant component of central glucose hypometabolism in HD patients. Here we review the main features of glucose metabolism and transport in the brain in physiological conditions and how these processes are impaired in HD, and discuss the potential ability of strategies aimed at increasing intracellular energy levels to counteract neurological and motor degeneration in HD patients.